Performance Evaluation of a Standalone PV-Hydrogen Power System for Continuous Supply Reliability in Brack Al-Shatti - Salim, Elsadic; Astel, Alfaitory; Latiwash, Ibrahim; Fakher, Massoud; Irhouma, Mukhtar; Ahmad, Suliman; Abduallah, Abduallah; Nassar, Yasser (Wadi Alshatti University Journal of Pure and Applied Sciences, 2026)
This study aims to evaluate the techno-economic feasibility of a standalone (off-grid) energy system in Brack Al-Shatti, utilizing a green hydrogen production and recovery cycle as a long-duration energy storage solution, aligned with the National Vision 2050 and the Paris Climate Agreement. The methodology employs a precise energy balance integration, featuring a 511.1 MW photovoltaic field supplying a 198.4 MW electrolyzer, coupled with a hydrogen storage capacity of 20,704 m³ at an operating pressure of 100 bar. To ensure operational reliability and uninterruptible supply, the system is reinforced with a 171.5 MW fuel cell and a 227.5 kW Reverse Osmosis (RO) desalination unit to provide the high-purity water essential for the electrochemical process. The results demonstrate the system’s capability to fully meet the target annual electrical load of 590,018 MWh with 100% self-reliance. Despite substantial capital expenditures (CAPEX) estimated between $1.52 and $2.96 billion, the financial analysis reveals a competitive Levelized Cost of Energy (LCOE) of approximately $0.097/kWh when environmental credits are integrated. Environmentally, the system prevents the emission of 611,850 tons of CO2 annually, generating an indirect fiscal saving exceeding $52 million. The study concludes that the success of this model in Brack Alshatti serves as a cornerstone for transforming Southern Libya from an energy- consuming region into a regional hub for clean energy exportation, contingent upon global technology price flexibility and local logistical infrastructure development.